Are the relevant provisions of the Rotterdam Rules dealing with the identification of the carrier an improvement over the Hamburg and Hague-Visby Rules? - Samkange, Ruvarashe Kudzai (Shipping Law Unit, 2018)
The carrier identity problem is one that may arise in the context of the international carriage of goods by sea. This problem may arise in a variety of ways particularly when the carriage arrangements are complex or where there is no clear documentary evidence that may assist in the identification of the contractual carrier. The identification of the carrier is a question of fact that can be drawn from the circumstances surrounding the carriage contract and the transport documents issued in relation to the carriage of goods by sea. The core question in solving this problem is to ask is which party assumed responsibility for the carriage and delivery of the goods. There are various ways in which the carrier may be identified, however, it must be understood that the solution to the carrier identity problem is not so straightforward. The carrier identity problem can stem from the way in which these methods of identifying the carrier are executed in practice. The dissertation argues that the relevant provisions of the Rotterdam Rules relating to the identity of the carrier are an improvement on the relevant provisions in the Hague-Visby Rules and the Hamburg Rules in that they provide a more coherent and clearer solution to the carrier identity problem than the previous carriage regimes did as well as providing solutions where the previous dispensations did not. The dissertation does not address all manifestations of the carrier identity problem, instead three specific examples are used to highlight the various aspects of the fundamental problem in order to assess whether the Rotterdam Rules have been an improvement on the previous carriage regimes. These specific instances are; when there is insufficient information to identify person or entity that is the contractual carrier; when there are different contractual and performing parties and; the carrier identity problem in the context of multimodal transportation. The Rotterdam Rules aim to be more an extensive and uniform set of Rules attempting to be a reflection of modern commercial practice in tune with the current trends and practices. The Rotterdam Rules provide what can be labelled as pre-emptive and reactive measures which seek to prevent the carrier identity problem from arising as well as providing solutions for situations when the carrier identity problems arise. This dissertation assesses whether the Rotterdam Rules, as compared to the previous dispensations do provide solutions to the carrier identity problems as well as whether such solutions are adequate to fully address these identified problems.